Demythologising the Given: Schlick, Cornelius, and Adorno contra Husserl - Andreas Vrahimis (Philosophies, 2024)
After the attempt at collaboration between the Frankfurt School and the Vienna Circle failed in the late 1930s, Adorno stood at the forefront of critical theory’s polemics against ‘positivism’. Given these later polemical exchanges, some of the tendencies common to both movements have remained overlooked. Among these is their opposition to the phenomenological tradition. This paper focusses on certain features common to Schlick’s and Adorno’s critical responses to Husserl. The Machians, including Adorno’s supervisor Hans Cornelius, were targeted by Husserl’s onslaught against psychologism in 1900. The young Schlick’s Machian background had motivated his contribution to the Psychologismusstreit, in the context of which he launched a series of objections against Husserl’s ‘independence theory of truth’. Adorno’s later doctoral dissertation under Cornelius was also motivated by the effort to defend his master against Husserl’s objections. Schlick’s criticisms intensified in later works, where Husserl’s epistemology of intuition is seen as yet another instance of the widespread confusion between knowledge and acquaintance. Schlick’s warnings against Husserl’s turn towards the irrationalist fashions of his day find their echo in Adorno’s ‘Metakritik’. Apart from their broad agreement in how they understand Husserl’s positioning within his context, Schlick and Adorno also develop a similar criticism of Husserl’s account of intuition as failing in its aspiration to discover unmediated givenness, which it confuses with mediated conceptual knowledge. Unfortunately, while Adorno explicitly acknowledges Schlick’s critique of Husserl, he also misconstrues it as a scientistic rejection of metaphysical nonsense, thus failing to acknowledge the proximity to his approach.